Reward responses to vicarious feeding depend on body mass index - Järvinen, Lili; Santavirta, Severi; Putkinen, Vesa; Karlsson, Henry K.; Seppälä, Kerttu; Sun, Lihua; Hudson, Matthew; Hirvonen, Jussi; Nuutila, Pirjo; Nummenmaa, Lauri (Springer Nature, 2025)
Eating is inherently social for humans. Yet, most neuroimaging studies of appetite and food-induced reward have focused on studying brain responses to food intake or viewing pictures of food alone. We used functional magnetic resonance imaging (fMRI) to measure haemodynamic responses to “vicarious” feeding. The subjects (n = 97) viewed series of short videos representing naturalistic episodes of social eating intermixed with videos without feeding/appetite-related content. Viewing the vicarious feeding (versus control) videos activated motor and premotor cortices, thalamus, and dorsolateral prefrontal cortices, consistent with somatomotor and affective engagement. Responses to the feeding videos were negatively correlated with the participants’ body mass index. Altogether these results suggest that seeing others eating engages the corresponding motor and affective programs in the viewers’ brain, potentially increasing appetite and promoting mutual feeding.